Metabolic Syndrome in Patients Having Cholelithiasis at Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: To evaluate the metabolic syndrome (MS) in patients having cholelithiasis at tertiary care hospital Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at General Surgery Department of Liaquat University Hospital Hyderabad from November 2015 to May 2016.Materials and Methods: Both genders were included in the study, with diagnosis of cholelithiasis on ultrasound by senior sinologist. Before surgery the selected cases metabolic syndrome was assessed. MS criteria were defined according to 3rd Report of the National Cholesterol Education Program.24 Metabolic syndrome was carried out in all the cases clinically and fasting blood for thee fasting blood sugar and lipid profile. After results all the data was entered in the proforma. Results: In this study majority of patients i.e. 42 (38.18%) belonged to age group of 45-50. 71(64.54%) patients were female. 60(54.55%) patients having cholilithiasis duration less than 5 years, 45.45% had more than 5 years.40(35.46%) patients have raised BMI. Regarding BP of patients 15 (13.63%) had raised systolic BP and 18 (16.36%) patients had raised diastolic BP. Fasting RBS elevated was in 40 cases. Total 29(26.36%) patients were associated with metabolic syndrome.Conclusion: Metabolic syndrome is big prevalent and also can say a big risk factor for cholelithiasis. Female gender and older age peoples are highly affected by with gall stone due to metabolic syndrome.